PENGEMBANGAN KEGIATAN KEWIRAUSAHAAN PADA MATA PELAJARAN PRAKARYA DAN EKONOMI KREATIF BAGI TUTOR DI PKBM 11 MANGGARAI - Hesti Rian; Ria Estiana; Eko Hadi Prayitno; Darmawan Darmawan; Nurul Giswi Karomah (POLITEKNIK LP3I JAKARTA, 2021)
The 2013 curriculum brings changes to the world of education, especially in entrepreneurship education and crafts and creative economy subjects. The concept of the Creative Economy is a concept in the new economic era whose main supports are information and creativity, where ideas and stock of knowledge from Human Resources (HR) are the main factors in economic activity. Creative ideas that come from entrepreneurs require a touch of innovation to sell in the market. The innovation needed by entrepreneurs is the ability to add value to products and maintain product quality by paying attention to market orientation. The increase in the use value of a product will also increase the selling power of the product in the market, because there is an increase in the economic value of the product for consumers. During the covid-19 pandemic, tutors felt obstacles in implementing craft subjects and the creative economy, especially in helping students market business products. Prior to the COVID-19 pandemic, the products were marketed through market day activities which were held after the craft and creative economy subjects took 4 meetings.The solution provided by the Jakarta LP3I Polytechnic to PKBM 11 Manggarai, South Jakarta is to provide Entrepreneurship Activity Development Training in Craft and Creative Economy Subjects with the theme